2015
DOI: 10.1371/journal.pone.0131641
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Age and Cognition on a Cross-Cultural Paediatric Adaptation of the Sniffin' Sticks Identification Test

Abstract: ObjectivesTo study the effects of age and cognition on the performance of children aged 3 to 18 years on a culturally adapted version of the 16 item smell identification test from Sniffin' Sticks (SS16).MethodsA series of pilots were conducted on 29 children aged 3 to 18 years old and 23 adults to produce an adapted version of the SS16 suitable for Brazilian children (SS16-Child). A final version was applied to 51 children alongside a picture identification test (PIT-SS16-Child) to access cognitive abilities i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 35 publications
0
16
1
1
Order By: Relevance
“…To avoid the bias of age-dependent odor learning, we included young children who were old enough to understand and perform an odor identification task. Recently, Cavazzana and colleagues reported that odor identification tasks in children younger than 5 years of age to be unreliable 48 , considering previous studies 39,46 . Although some studies have claimed that children as young as 3-4 years are able to perform an odor identification task [28][29][30] , results must be evaluated with caution.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To avoid the bias of age-dependent odor learning, we included young children who were old enough to understand and perform an odor identification task. Recently, Cavazzana and colleagues reported that odor identification tasks in children younger than 5 years of age to be unreliable 48 , considering previous studies 39,46 . Although some studies have claimed that children as young as 3-4 years are able to perform an odor identification task [28][29][30] , results must be evaluated with caution.…”
Section: Discussionmentioning
confidence: 99%
“…To increase the number of anosmic children in our test validation, the age range of this population was 6-17 years. Previous studies have reported an increase in odor identification score with age 27,28,39,52 . Such an increase is not expected in children with ICA.…”
Section: Several Odor Identification Tests Have Been Developed For Chmentioning
confidence: 90%
See 1 more Smart Citation
“…Within each group, testing scores were not affected by the factor “age.” Several factors may contribute to the positive result, which includes verbal abilities, familiarity with odors, and cognitive capacity to identify certain odors. [ 28 , 30 ] These factors are associated with cognitive level and seem to develop with age. Cognition is known as a significant determinant of olfactory performance other than age.…”
Section: Discussionmentioning
confidence: 99%
“…13 This test has been used for adults and children and adolescents, including studies providing normative data for children and adolescents that can be used in clinical settings. [14][15][16] The olfactory threshold test for n-butanol was conducted by presenting a participant with 16 numbered triplets of felt-tip pens, using a single-staircase and 3 alternative forced-choice procedures. Three pens were placed in a random order, 1 with the odorant and 2 others with the solvent alone.…”
Section: Measurements Of Olfactory Function Using Olfactory Threshomentioning
confidence: 99%